A ambivalência dos posicionamentos da oficialidade eclesiástica e a renovação carismática católica : uma proposta de interpretação - Mello, André Almeida de (2011)
The subject of this dissertation is the ambivalence that has been characteristic of the stances of the Brazilian catholic ecclesiastic hierarchy on the issue of the Charismatic Catholic Renewal (CCR). It starts discussing the origin, development and main characteristics of the CCR. Following, a historical perspective of the stances of the Latin American, particularly Brazilian, catholic ecclesiastic hierarchy is presented, which are marked by ambivalence. Finally, one interpretation of the motives and tendencies of the ambivalence of the stances of the Brazilian catholic ecclesiastic hierarchy is presented, based on the theoretical framework of Pierre Bourdieu’s concept of religious field and Max Weber’s use of the concept of sacred state.